Entomological Assessment of Onchocerca Species Transmission by Black Flies in Selected Communities in the West Region of Cameroon - Cabirou Mounchili Shintouo (Pathogens, 2020)
The enormity of the public health burden of onchocerciasis motivated the creation of various large-scale control programs that have depended principally on mass treatment of endemic communities with ivermectin for the elimination of the disease. Parasitological evaluation of Onchocerca species in the West Region of Cameroon indicates significant progress in the interruption of parasite transmission in some communities under ivermectin treatment. However, to verify the complete elimination of onchocerciasis, entomological assessment through O-150 PCR poolscreen of black flies is mandatory. Thus, in the present study, we assessed transmission of Onchocerca species using an O-150 PCR technique to screen pools of black flies—in seven onchocerciasis endemic communities (Makouopsap, Bankambe, Lemgo, Tsesse, Ndionzou, Kouffen, and Bayon) in Cameroon. Two thousand black flies were assessed—in each community—for the presence of Onchocerca species DNA. Our results show that the frequency of infective flies was 0.6% in Makouopsap and 0.0% in the other communities. On the other hand, the frequency of infected flies was 0.8% in Makouopsap, 0.2% in Bankambe, 0.1% in Bayon, and 0.0% in Lemgo, Tsesse, Ndionzou, and Kouffen. These results provide entomologic evidence for continuous transmission of Onchocerca species in Makouopsap, risk of active transmission in Bankambe, and Bayon, and a suppressed transmission in the four other studied communities.